1998
DOI: 10.1021/bi9802871
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Single and Double Mutations in Plastocyanin on the Rate Constant and Activation Parameters for the Rearrangement Gating the Electron-Transfer Reaction between the Triplet State of Zinc Cytochromecand Cupriplastocyanin

Abstract: The unimolecular rate constant for the photoinduced electron-transfer reaction 3Zncyt/pc(II) --> Zncyt+/pc(I) within the electrostatic complex of zinc cytochrome c and spinach cupriplastocyanin is kF. We report the effects on kF of the following factors, all at pH 7.0: 12 single mutations on the plastocyanin surface (Leu12Asn, Leu12Glu, Leu12Lys, Asp42Asn, Asp42Lys, Glu43Asn, Glu59Gln, Glu59Lys, Glu60Gln, Glu60Lys, Gln88Glu, and Gln88Lys), the double mutation Glu59Lys/Glu60Gln, temperature (in the range 273.3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 101 publications
(183 reference statements)
3
42
0
Order By: Relevance
“…These findings allow us to conclude that Arg-88 is a crucial residue not only for long range electrostatic attractions between Pc and PSI but also for electron transfer. It should be noted that glutamine at position 88 of spinach Pc has been replaced with asparagine, glutamate, lysine, and tyrosine with no significant changes in the kinetics of PSI reduction (27,28).…”
Section: Resultsmentioning
confidence: 99%
“…These findings allow us to conclude that Arg-88 is a crucial residue not only for long range electrostatic attractions between Pc and PSI but also for electron transfer. It should be noted that glutamine at position 88 of spinach Pc has been replaced with asparagine, glutamate, lysine, and tyrosine with no significant changes in the kinetics of PSI reduction (27,28).…”
Section: Resultsmentioning
confidence: 99%
“…In the cases of true and coupled ET, the observed ET rates are expected to be independent of viscosity [117]. A recent electron transfer kinetics study at various temperatures suggested that the FMN–heme IET in nNOS holoenzyme may be coupled to the pre-requisite conformational movement of the FMN domain [118].…”
Section: Mechanism Of the Fmn–heme Iet In Nosmentioning
confidence: 99%
“…[4][5][6] However, even for small and well-characterized proteins such as cytochrome c (CytC), [7,8] an intrinsic CT mechanism in "homogeneous" systems is difficult to recognize conclusively as a consequence of the extra structural and dynamic environmental complexity introduced by the participating redox partner. [4,5,[9][10][11] The covalent attachment of "small" complex ions as the redox counterparts at different external sites of CytC [12,13] does not warrant sufficiently smooth variation of intrinsic parameters, such as an electronic coupling (correlated with the CT distance; see below), because of the highly inhomogeneous nature of the protein interior. In this context, artificial bioelectrochemical devices made of electrode-deposited self-assembled monolayer (SAM) films of variable composition and thickness, and CytC or other redox proteins attached or freely diffusing to the SAM terminal groups (also subject to wide variations), were proven to be systems with wellcontrolled variable parameters, and hence suitable for fundamental studies [8,[14][15][16][17][18] and some technological applications.…”
mentioning
confidence: 99%
“…[18] Somewhat larger slopes were found for an ET within the "homogeneous" system involving zinc-substituted CytC, and wild-type and mutant cupriplastocyanin, which ranged from 0.7 to 0.9. [9][10][11] Interestingly, full viscosity control (d % 1) has been observed for photoinduced CT from the artificial Rucoordinated polypeptide electron donor to ferri-CytC, [48] which occurs through the loosely bound (encounter) complex as opposed to the "preformed" (tight) complex involving the same reactants (d % 0.6); both patterns occur simultaneously. The latter findings closely match the whole pattern of CytC bioelectrochemical CT in both the tightly bound and freely diffusing (to Au-deposited SAMs comprising w-COOH and w-OH) regimes, respectively.…”
mentioning
confidence: 99%